Devising a doctoral program at the Center of Education Studies of the Universidad Central de las Villas - Torres Alfonso, Aida María; Padilla Cuéllar , Yanet; Veitia Arrieta, Isabel Julia (Transformación, 2024)
Objective: The paper aims at describing a pedagogical conception that contributes to the process of doctoral training in Education at "Gaspar Jorge García Galló" Center for Education Studies at "Marta Abreu" Central University of Las Villas. Methods: The dialectical-materialistic method is assumed in its unit of the theoretical and empirical approaches, and the qualitative and quantitative methods; information was collected by data analysis, participant observation, documentary analysis and statistical processing displayed in tables and graphs. Result: The main finding is the description of the doctoral program in Education devised at the UCLV and its underlying theoretical framework by accounting the descriptors followed in the study: program structure, program research component, program execution and scientific retrieval potentials. Conclusion: The devised program is effective for the doctoral training process, it makes possible to increase the results in doctoral training, increases the research competencies and innovative capacities of graduates, causing a positive impact in the regional educational system and society. The program has been certified as excellent by the Junta Central of Acreditación (National Cortication Board) and awarded by the AUIP in 2018.